Sugar-Sweetened Beverage Consumption and Risk of Visceral Fat Accumulation Among University Students in Thailand - Phisit Pouyfung; Jaruneth Petchoo; Suwichak Chaisit (Roczniki Panstwowego Zakladu Higieny)
Background Increased consumption of sugar-sweetened beverages (SSBs) is associated with obesity and metabolic health risks.